Vitamin-D in Women with Primary Infertility in a Tertiary Care Centre in the Southeast Region of Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Introduction: Infertility affects 9–18% of the population, with vitamin D deficiency being a potential contributing factor. This study evaluates the association between vitamin D levels and primary Infertility in women attending a tertiary care centre in Southeast Bangladesh.Methods: A cross-sectional study was conducted at Chittagong Medical College Hospital’s(CMCH) Infertility Unit over one year( February 2020 to January 2021). Ninety-two women with primary Infertility were recruited based on specific inclusion criteria. Data collection included demographic details, clinical history, hormonal profiles, and vitamin D levels measured via Chemiluminescent Microparticle Immunoassay. Vitamin D status was classified according to the 2011 Endocrine Society guidelines. Statistical analysis was performed using SPSS version 23.Results: All the participant’s Vitamin D level were found less than normal. The majority (75%) of women had insufficient (